Characterization of bone marrow aspirate reports in dogs and cats: A retrospective study - Roldán-Carvajal, Ingrid J; Alzate-Velásquez, David; Muñoz-Duque, Julián D; Mesa-Oquendo, Andrés F; Salazar-Flórez, Jorge E; Jaramillo-Arbeláez, Patricia E (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Bone Marrow Aspirate (BMA) allows the study, staging and monitoring of multiple conditions with bone marrow involvement. The BMA report is a crucial component of the post-analytical stage and significantly influences the veterinarian’s understanding and decision-making process. Objective: To describe the zoographic, clinical, and quality characteristics of BMA reports, as well as the frequency of diagnoses and associated factors in dogs and cats treated at veterinary centers in Colombia from 2012 to 2023. Methods: This was a cross-sectional descriptive study. Data on zoographic and clinical variables were extracted from BMA reports and consultations; the frequency of diagnoses and associated factors were determined. Adherence to reporting quality was evaluated using established guidelines for BMA in dogs, cats, and humans. Results: A total of 135 BMA reports were reviewed from eight veterinary institutions: 116 for dogs and 19 for cats, with a mean age of 5.22 ± 3 years; 53% were males. The most common indication for BMA was anemia, alone or with other abnormalities. The least adhered-to reporting elements were puncture site (91.9%), relevant clinical data (85.2%), and morphological evaluation by cell line (52.6%). Additionally, 27.4% of the reports were excluded due to poor sample quality. The most frequent diagnosis in dogs was hypoplasia (36.1%), while in cats, it was neoplasia (40.0%). Erythroid hyperplasia and neoplasms were more prevalent in males, whereas granulocytic hypoplasia was more common in females. Conclusions: BMA as a diagnostic tool in dogs and cats in Colombia is rare. A significant proportion of samples did not meet quality criteria, and there was low adherence to reporting guidelines.